Perancangan Sistem Informasi Pembelajaran Online Berbasis Website di MA Al Barokah Malangbong Garut - Furqon, Muhamad; Rohmanto, Ricky (Jurnal Accounting Information System (AIMS), 2024)
dEvelopment of information technology (IT) has driven its integration into various aspects of life, including education. MA Al Barokah, an educational institution in Malangbong, Garut, faces the challenge of using an unoptimal internet network for teaching and learning activities. Currently, the learning process is still conducted in a conventional face-to-face manner in the classroom, which has constraints such as lesson time that can only be done during school hours and depends on the physical presence of teachers and students. To address this problem, the study aims to design and implement a web-based learning information system (e-learning) at the MA Al Barokah. It is expected to facilitate learning without time and place constraints, as well as allow the teaching and learning process to continue even if teachers or students are not physically present. The development method used is Unified Modeling Language (UML) and integrates the concept of Rational Unified Process (RUP) with the PHP programming language and MySQL database. The results of the implementation of this system show that e-learning can improve the flexibility and effectiveness of the teaching and learning process at the MA Al Barokah, as well as have a positive impact on improving the service and confidence of students' parents in the school.